Taxonogenomics description of Parabacteroides timonensis sp. nov. isolated from a human stool sample. Issue 4 (11th October 2018) - Bilen, Melhem; Mbogning Fonkou, Maxime Descartes; Khelaifia, Saber; Tomei, Enora; Cadoret, Frédéric; Daoud, Ziad; Armstrong, Nicholas; Bittar, Fadi; Fournier, Pierre‐Edouard; Raoult, Didier; Dubourg, Gregory
Abstract: Intensive efforts have been made to describe the human microbiome and its involvement in health and disease. Culturomics has been recently adapted to target formerly uncultured bacteria and other unclassified bacterial species. This approach enabled us to isolate in the current study a new bacterial species, Parabacteroides timonensis strain Marseille‐P3236 T, from a stool sample of a healthy 39‐year‐old pygmy male. This strain, is an anaerobic, gram‐negative, nonspore‐forming motile rod. Its genome is made up of 6, 483, 434 bp with 43.41% G+C content, 5046 protein‐encoding genes, and 84 RNA genes. We herein provide the full description of Parabacteroides timonensis strain Marseille‐P3236 T through the taxonogenomic approach. Abstract : In the present work, we report the isolation of a new bacterial species in Parabacteroides genus by the means of Culturomics and its description by taxono‐enomics approach.